Vocabulary teaching in korean language [Kore dili programinda söz varliğinin öğretimi] - (:unkn) unknown (T.C. Milli Egitim Bakanligi, 2016)
Finland and Korea (South Korea) did manage to reach the highest scores in the years of 2000, 2003, 2006 and 2009 on literacy field of PISA assesments. These results proved that the agglutinative languages such as Finnish and Korean appeared to be more effective than the other languages in terms of developing reading and cognitive skills. Turkish is also an agglutinative language which is listed in the Ural Altaic language group like Korean. Therefore, it is needed to examine teaching processes of Korean. Vocabulary teaching is one of the topics which should be focused on during examining the development of a language. Vocabulary is defined as a whole includes words, idioms, proverbs and other sayings which take place in Turkish language program book. In this article, the language teaching program of Korea which ranks among the most successful countries in reading literacy field in Pisa assesments will be examined and the studies in relation to vocabulary teaching in Korean will be also included.
Keywords: Korean; Korean language; Vocabulary; Vocabulary teaching